Sistem Informasi Point of Sale Berbasis Web pada Toko Afridah Cake - Rahman, M Noer; Abdullah, Abdullah; Rianto, Bayu (Universitas Merdeka Malang, 2022)
The development of internet technology in Indonesia, especially in the use of computer technology for data processing, is also a concern in the business world. Through computerized data processing, all items that have been sold can be quickly identified, along with their advantages. Toko Afridah Cake is a business that sells various types of cakes and snacks in Tembilahan which is still with an offline transaction system. Therefore, it is necessary to build a point of sale information system at the Afridah Cake store so that it makes it easier to develop a business. Researchers use the SDLC (System Development Life Cycle) system development method and use pieces analysis. The system is designed using three levels of users, namely admin, cashier, and consumer. The system can be used to exist at Toko Afridah Cake because it has passed the blackbox testing stage without any errors. This web-based point of sale system makes it easier for store owners, especially to monitor the transaction process in the store without having to come to the store because the system is web-based so that it can be accessed anywhere while still being able to connect to the internet.